Evaluation of Natural Radioactivity in Granite and Marble used as Flooring Materials in Baghdad Province/ Iraq - Zeyad, Zaid; AL-Fatlawy, Yaaroub Faleh Khalf (Iraqi Journal of Science, 2018)
Twenty four samples of various granites and marble used common as flooring materials were collected from many factories and market in Baghdad Province, Iraq. Natural radioactivity of 226Ra, 232Th and 40K in the samples was measured by using high purity germanium detectors with an efficiency of 40%. The Specific activity concentration in granite samples ranged from 9.20 to 79.64 Bq/kg, 10.50 to 229.40 Bq/kg and 185.30 to 1391.20 Bq/kg for 226Ra, 232Th and 40K, respectively. The estimated of radiological parameters: radium equivalent activity (Req), activity concentration Index (I) and hazard indices (internal (Hin) and External (Hex)) that associated with the radiation hazard in the samples. The results of activity specific concentrations and radiological parameters of 226Ra, 232Th and 40K were compared with the reported data of the worldwide limit of building materials.